REPRESENTATION OF HUMAN NATURE IN ANIMATED CHARACTERS: A SEMIOTIC STUDY OF SHAUN THE SHEEP SERIES - Wildani, Nurul; Lestari, Nurul; Hasbi, Muh. (Faculty of Languages and Literature, Universitas Negeri Makassar, 2024)
AbstractThe purpose of this research is to analyze the denotative, connotative, and mythical meaning of the characters in Shaun the Sheep series and to reveal the representation of human nature in the animated characters of Shaun the Sheep series. This research uses a qualitative descriptive approach and uses Roland Barthes semiotic analysis. The focus of this research is visual and gesture analysis. The results of this study include (1) Showing the existence of denotative, connotative and mythical forms of meaning. (2) Representing human nature in